Endothelial Protein C Receptor Could Contribute to Experimental Malaria-Associated Acute Respiratory Distress Syndrome - Luana dos Santos Ortolan; Michelle Klein Sercundes; Gabriel Candido Moura; Thatyane de Castro Quirino; Daniela Debone; Douglas de Sousa Costa; Oscar Murillo; Claudio Romero Farias Marinho; Sabrina Epiphanio (Journal of Immunology Research)
The severity of Plasmodium falciparum malaria is associated with parasite cytoadherence, but there is limited knowledge about the effect of parasite cytoadherence in malaria-associated acute respiratory distress syndrome (ARDS). Our objective was to evaluate the cytoadherence of infected red blood cells (iRBCs) in a murine model of ARDS and to appraise a potential function of endothelial protein C receptor (EPCR) in ARDS pathogenesis. DBA/2 mice infected with P. berghei ANKA were classified as ARDS- or hyperparasitemia- (HP-) developing mice according to respiratory parameters and parasitemia. Lungs, blood, and bronchoalveolar lavage were collected for gene expression or protein analyses. Primary cultures of microvascular lung endothelial cells from DBA/2 mice were analyzed for iRBC interactions. Lungs from ARDS-developing mice showed evidence of iRBC accumulation along with an increase in EPCR and TNF concentrations. Furthermore, TNF increased iRBC adherence in vitro. Dexamethasone-treated infected mice showed low levels of TNF and EPCR mRNA expression and, finally, decreased vascular permeability, thus protecting mice from ARDS. In conclusion, we identified that increased iRBC cytoadherence in the lungs underlies malaria-associated ARDS in DBA/2-infected mice and that inflammation increased cytoadherence capacity, suggesting a participation of EPCR and a conceivable target for drug development.